IMPLEMENTATION OF THE COMPETENCE APPROACH IN THE UNIVERSITY BY ADDITIONAL STUDENTS TRAINING - Nina Vasilevna Koblova; Anna Dmitrievna Barbara (Sovremennye Issledovaniâ Socialʹnyh Problem, 2014)
The article deals with the factors affecting the demand for graduates in the labor market. In the paper it is proved that there is need of the creation of additional conditions for the development of competencies through university innovation infrastructure. Methodology: analysis of employer requirements for graduates, empirical research on the students’ representations of readiness for professional work. Result: competence model of the graduate is presented, the innovation infrastructure of the university for implementation of the competency approach in the process of training students is offered.